2014
DOI: 10.1371/journal.pone.0110490
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Music-Evoked Sadness: An Online Survey

Abstract: This study explores listeners’ experience of music-evoked sadness. Sadness is typically assumed to be undesirable and is therefore usually avoided in everyday life. Yet the question remains: Why do people seek and appreciate sadness in music? We present findings from an online survey with both Western and Eastern participants (N = 772). The survey investigates the rewarding aspects of music-evoked sadness, as well as the relative contribution of listener characteristics and situational factors to the appreciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
212
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(244 citation statements)
references
References 80 publications
21
212
3
2
Order By: Relevance
“…Taruffi and Koelsch [23] expanded this explanation by bringing in the role of memories and deliberate savouring of emotions, whereas Juslin [33] also evoked the same rationale by explaining that sad music may combine two independent mechanisms, contagion of negative emotion and the aesthetic judgment mechanism that leads to an overall pleasurable response. Sachs and his colleagues 120 [34] interpreted the paradox from the perspective of adjusting homeostatic imbalances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Taruffi and Koelsch [23] expanded this explanation by bringing in the role of memories and deliberate savouring of emotions, whereas Juslin [33] also evoked the same rationale by explaining that sad music may combine two independent mechanisms, contagion of negative emotion and the aesthetic judgment mechanism that leads to an overall pleasurable response. Sachs and his colleagues 120 [34] interpreted the paradox from the perspective of adjusting homeostatic imbalances.…”
mentioning
confidence: 99%
“…Mechanisms such as episodic memories, emotional contagion, and eval- 75 uative conditioning have been offered to account for music-induced sadness in particular [23]. A later update to the mechanisms also includes aesthetic judgement (which has been taken to explain the enjoyment of sad music as well; [24]).…”
mentioning
confidence: 99%
“…Also, Wildschut et al (2006) and Sedikides et al (2008) suggest that sadness and negative mood is often a trigger of nostalgia. A recent study by Taruffi and Koelsch (2014) suggests that nostalgia is actually the most frequent emotion evoked by sad music. This could be surmised to be an effect of episodic memory, in the sense that the melancholic and sad stimuli trigger episodic memories and hence nostalgia.…”
Section: ) Learningmentioning
confidence: 99%
“…Juslin (2011) proposes that on the basis of previous survey studies both nostalgia and longing are among the most common emotions evoked by music, and nostalgia's prominence among music-induced feelings has also been pointed out by, for example, Zentner and Eerola (2010). In a recent study by Taruffi and Koelsch (2014), nostalgia was indicated as the most frequent emotion evoked by sad music among a large and heterogeneous pool of participants. Interestingly, the prevalence of nostalgia in music is not only limited to felt emotional experiences, since it is common also as a perceived emotion in music (Juslin & Laukka, 2004).…”
mentioning
confidence: 96%
“…Thus, people often report that they prefer to listen to sad music when they are alone, or when feeling lonely (Peltola & Eerola, 2016;Taruffi & Koelsch, 2014;Van den Tol & Edwards, 2013).…”
mentioning
confidence: 99%